2005
DOI: 10.1007/s10384-005-0199-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Internal Limiting Membrane Peeling in Vitrectomy on Diabetic Cystoid Macular Edema Patients

Abstract: Visual acuity improved with vitrectomy for diabetic cystoid macular edema in both groups. ILM peeling was not found to improve visual acuity postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…There are three reports of ICG use in patients undergoing surgery for diabetic macular oedema. Two showed a favourable safety profile, 44,45 whereas one showed visual field defects, 42 making it difficult to draw a conclusion.…”
Section: Surgery For Diabetic Macular Oedemamentioning
confidence: 97%
“…There are three reports of ICG use in patients undergoing surgery for diabetic macular oedema. Two showed a favourable safety profile, 44,45 whereas one showed visual field defects, 42 making it difficult to draw a conclusion.…”
Section: Surgery For Diabetic Macular Oedemamentioning
confidence: 97%
“…In recent years pars plana vitrectomy (PPV) with internal limiting membrane (ILM) removal has been reported to be beneficial in resolution of macular edema and improved visual acuity in patients with diffuse diabetic macular edema, both with and without vitreo-macular interface abnormalities [3,6,9,12]. The data from these studies included patients from potentially different prognostic groups such as presence of macular traction and taut thickened posterior hyaloid (TTPH).…”
Section: Introductionmentioning
confidence: 98%
“…Although several studies have reported that ILM removal enhanced the effectiveness of vitrectomy for DME [12,23,24] , there are also some reports that showed that the difference in the outcome of vitrectomy with or without ILM peeling was not significant [21,22,25] . Because ICG was used to make the ILM more visible in most of these studies, our results are consistent with those reports.…”
Section: Discussionmentioning
confidence: 99%